The Influence of Muslim-Friendly Hotels on the Satisfaction of Muslim Visitors - Nur'aeni, Nur'aeni; Setiawan, Setiawan; Nugraha, Galih (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
This study aims to analyze the influence of Muslim-friendly hotel attributes on the satisfaction of Muslim visitors in Bandung City. The independent variables studied include worship facilities, Islamic entertainment, halal food, Islamic clothing, and Islamic morality, with visitor satisfaction as the dependent variable. The study used a quantitative approach with a survey method of 164 respondents who had stayed at Sharia hotels in Bandung. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) through the WarpPLS application. The results showed that three variables, namely Islamic entertainment, halal food, and Islamic morality, had a positive and significant effect on visitor satisfaction. Conversely, the variables of worship facilities and Islamic clothing had no significant effect. These findings indicate that visitor satisfaction with sharia hotels is more influenced by the religious and moral values applied by the hotel than by physical or symbolic attributes alone. The Islamic morality variable is the most dominant factor in increasing satisfaction, indicating the importance of applying Islamic ethics in hotel services. Theoretically, the results of this study reinforce the concept of Islamic hospitality, which emphasizes the importance of integrating spiritual values and service quality in halal tourism.